Design and characterization substrate integrated waveguide antenna for WBANS application - Mustafa Mohammed Jawad Abed; Nik Noordini Nik Abd Malik; Noor Asniza Murad; Mona Riza Mohd Esa; Mohd Riduan Ahmad; Ola Hussein Abed Al Radh; Ali Abdulateef Abdulbari; Yaqdhan Mahmood Hussein; Fahad Taha Al-Dhief (Institute of Advanced Engineering and Science, 2022)
Millimetre-wave frequencies are defined as one of the front-runner contenders for body-centric wireless communication. In this study, low-profile antenna with the substrate integrated waveguide (SIW) has been proposed that operate in the band of the millimetre-wave frequency that has been centred at 60 GHz. The proposed antenna has been implemented with the use of the FR4 substrate with εr and tangent loss of 4.3 and 0.025, respectively. The substrate height and size are 1.5875 mm and 20 mm x 20 mm, respectively. The performance of the antenna is evaluated in off-body (free space) and on-body (human voxel model), through simulation. The proposed antenna has an ultra-wideband (UWB) and a specific absorption rate the maximal (SAR) for (10 g) is 0.0344815 W/kg and for (1 g) is 0.0184723 W/kg. It achieves 74% and 63% efficiency in the off and on-body scenario, respectively. The small antenna with the exceptional matching of impedance, low SAR, broad bandwidth, and good efficiency, a good voltage standing wave ratio good (VSWR), and good front-to-back ratio (FBR). As a result, its characteristics make it one of the best potential candidates for the simultaneous transmission and reception of data at (mm-wave) band for WBAN applications.